Pet cancer cases and patterns of treatment at a Spanish veterinary teaching hospital: a retrospective study from 2015 to 2024 - Beatriz Romero; Julen Susperregui; Raquel Díez; E. Milena Vazquez; Cristina Lopez; Raúl de la Puente; M. Jose Diez; Nelida Fernandez; Jose M. Rodriguez-Altonaga; Ana M. Sahagun (Frontiers in Veterinary Science, 2025)
Cancer is one of the most common causes of death for companion animals. The study aimed to describe the characteristics of the clinical cases of pets attending at the Veterinary Teaching Hospital (University of Leon, Spain) and diagnosed with tumors. A retrospective study was carried out between 2015 and 2024. A total of 123 animals comprising 107 dogs and 16 cats were obtained from the clinical records. A mean annual incidence risk of 530 of 100,000 animals was calculated. Most animals were dogs (87.0%), females (62.6%), purebred (77.2%) and aged (78.9%). Tumors were mainly malignant (87.8%), they were of epithelial origin (40.7%), and mostly located in mammary glands (27.6%) or skin/mucosa (26.8%). Carcinoma (35.8%) and lymphoma (19.5%) were the major histological types. Almost half of the animals underwent surgical treatment (42.3%). Chemotherapy was administered to 37.4% of the animals, mostly by the oral route. QL01E (protein kinase inhibitors) was the main pharmacological group employed. Concomitant treatments and dietary supplements were also used. Euthanasia was applied to 26.8% of the animals.